ChemInform Abstract: Copper‐Catalyzed Oxidative C‐H Amination: Synthesis of Imidazo[1, 2‐a]‐N‐Heterocycles from N‐Heteroaryl Enaminones. Issue 51 (December 2015) - Reddy, K. Ranjith; Reddy, A. Siva; Shankar, Ravi; Kant, Rajni; Das, Parthasarathi
Abstract: Under ligand‐ and base‐free conditions imidazole‐containing heterocycles are formed in the presence of copper(I) salts.